Implementasi Kebijakan Pendidikan Inklusif - * Prastiyono (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2013)
The Indonesia Government has commitments to organize inclusive education, that is to give the widest chance and access to all children including children with special needs to receive good quality of education dan appropriate to the need of student individual without discrimination. But on the reality, there are still lot of school-aged children with special needs haven’t got chance to receive education yet. This conditions are caused by many barriers including the social conditions of the civilizations. Another barriers come from schools who organize inclusive education still unable to organize inclusive education optimally. So that these inclusive education organizer isn’t yet unable to well developed at present. This research aims to analyze the implementation of inclusive education policy in Galuh Handayani School Surabaya and analyze factors that affect the implementation of inclusive education in creating quality of education in Galuh Handayani School Surabaya. This research focuses are, to observe the behavior of implementor from City Education Office and implementor school institution in socializing inclusive education policy, to observe the execution of working program from teachers in learning process in Galuh Handayani inclusive school Surabaya, to observe execution of inclusive education learning process and to observe execution of evaluation and inclusive education management monitoring. Qualitative descriptive is used to analyze datas. This research results show: first, that implementation of inclusive education in Galuh Handayani isn’t optimal or well performed yet. That can be reflected from indications like: (1) not all teachers able to perform inclusive education well, (2) not all parents understand knowledges about inclusive education. Second, factors that affect the success or failure of inclusive education policy implementation are communication factor: that is socialization only held two encounters in one semester. Resources factor include: not all teachers have ability and understanding about inclusive education and fund limitation to develop inclusive education. Disposition factors include: not all teachers have good attitude and behavior in performing their tasks and functions. Also bureaucracy structure factors from implementor: well rated because they perform their tasks based on operational standard and their organization structure is lean.Keywords: Policy Implementation and Inclusive Education